TUBULAR JOINT STRENGTH MODELS IN API RP2A WSD, API RP2A LRFD AND ISO 19902 - Sambu Potty, Narayanan (2010)
Working Stress Design is currently used in the design of jacket platforms in Malaysia. Worldwide LRFD codes are being developed. To adopt LRFD code, calibration of resistance factors for joints is necessary in order that new joint designs have the same reliability as the existing designs. Tubular joints are classified as simple, overlapping, congested or complex. Simple joints are further classified as K, T, Y or cross joints based on their configuration and load pattern. As a part of the ongoing research, the developments of the tubular joint strength models and their philosophy were studied. The joint strength models of API RP2A WSD (21st edition including 2nd supplement), API RP2A LRFD and ISO 19902 are presented and compared. The comparison includes the capacity of joints, relative joint and member strength, joint classification, joint detailing and the safety format. The conclusions from the study are reported. All codes use essentially the same equations with the differences for finding the characteristic force in respect of axial and moment resistance. Differences occur in the Strength factor (Qu) and the chord effect factor (Qf) leading to differences in the characteristic strengths calculated. ISO code is based on the latest research and has incorporated many changes.